Remediation of tetracycline from aqueous solution through adsorption on g-C3N4-ZnO-BaTiO3 nanocomposite: Optimization, modeling, and theoretical calculation - Ciğeroğlu, Zeynep; Kazan-Kaya, Emine Sena; El Messaoudi, Noureddine; Fernine, Yasmine; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Jada, Amane (Elsevier, 2023)
This study's goal is to treat a tetracycline (TC) antibiotic containing water with a graphitic carbon nitride (g-C3N4) based composite zinc oxide (ZnO)-barium titanate (BaTiO3) nanoparticles (g-C3N4-ZnO-BaTiO3) prepared from the extract of Olea Europaea leaves as an initiator under the ultrasound method. The FTIR, XRD, XPS, SEM, and TEM analyses were used for g-C3N4-ZnO-BaTiO3 nanocomposite. Response surface methodology-Box-Behnken design (RSM-BBD) was used to design the experiment and optimize the process parameters. TC adsorption ability of the g-C3N4-ZnO-BaTiO3 was evaluated and optimized by varying the pH, contact time, and initial TC solution concentration. RSM results demonstrated that g-C3N4-ZnO-BaTiO3 nanocomposite effectively improves the adsorption performance of g-C3N4-ZnO-BaTiO3 with optimal adsorption capacity of 209.19 mg g−1 at pH = 4.59 and for 180 min of contact time, and 60 mg L–1 of TC concentration. The whole adsorption process applies to the pseudo-second-order kinetics and the Freundlich isotherm model describes the best adsorption behavior of g-C3N4-ZnO-BaTiO3. Various characterization methods and zeta potential show the mechanism of adsorption of g-C3N4-ZnO-BaTiO3 toward TC, involving hydrogen bonds, electrostatic action, and π-π interactions. The quantum chemical calculations based on electrostatic potential maps, HOMO–LUMO distributions, and energy gaps showed that TC forms a stable cluster with g-C3N4-ZnO-BaTiO3, indicating its favorable adsorption. This indicates that the g-C3N4-ZnO-BaTiO3nanocomposite is an admirable adsorbent to remove antibiotics from water.
Keywords: DFT calculation; g-C3N4-ZnO-BaTiO3; RSM-BBD optimization; Tetracycline, adsorption